MIRZO ULUGBEK’S CONTRIBUTIONS TO EDUCATION - SAYUVDINOVA, Nilufar; G‘ULOMOVA , Muslima; BERDINAZAROVA, Munisa (Journal of Pedagogical and Psychological Studies, 2025)
This article examines the educational contributions of Mirzo Ulugbek, a renowned 15th-century scholar, astronomer, and ruler of the Timurid dynasty. As a great patron of science and education, he played a crucial role in the intellectual development of Central Asia. Ulugbek established the famous Ulugbek Madrasah in Samarkand, which became a leading center of learning, attracting scholars from various regions. His curriculum emphasized astronomy, mathematics, and rational sciences, reflecting his belief in the power of knowledge and critical thinking. Ulugbek himself actively participated in teaching and research, mentoring students and fostering a scientific community. His contributions laid the foundation for future advancements in mathematics and astronomy, influencing scholars for centuries. The article explores his educational reforms, teaching methods, and the long-lasting impact of his academic legacy on the Muslim world and beyond.